Locus of Control Memoderasi Pengganggaran Partisipatif terhadap Kinerja Manajerial (Studi Pada Pemerintah Daerah Kota Ternate) - Iwan S. Seber; Irsad Muhammad (Faculty of Economic and Business, 2020)
This study examines the effect of participatory budgeting on managerial performance with locus of control as a moderating variable. Proposional random sampling is a technique used in this study. There were 108 state civil servants within the regional apparatus organization in the city of Ternate as respondents in this study. The results of statistical tests show that the locus of control variable moderates the relationship between participatory budgeting and managerial performance. Partially, participatory budgeting has an effect on managerial performance. The implication of this research is that it can be used by regional apparatus organizations to design budget planning arrangements in the city of Ternate.